Structure and Vibrational Spectra - Dovesi, R.; Ferrari, A.; De La Pierre, Marco; Orlando, R.; Noël, Y. (Elsevier Ltd, 2013)
The way ab initio simulation provides the vibrational properties of crystalline compounds is described. The transverse optical (TO) and longitudinal optical (LO) branches of the infrared (IR) spectrum, the TO-LO splitting, the IR intensities, the vibrational contribution to the dielectric tensor, the Born effective charges, and the reflectance spectrum of large unit cell compounds such as forsterite (Mg2SiO4, 28 atoms/cell, olivine family) and grossular (Ca3Al2Si3O12, 80 atoms/cell, garnet family), are presented and discussed. Tools for the interpretation of the atomic motion for each normal mode are illustrated with examples.